Teacher Performance Analysis: Planning, Implementation, Evaluation, Communication, and Competency Development - Sufiah Mansur; Andi Syukri Syamsuri; Andi Paida (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study aims to analyze teacher performance in terms of planning, implementation, evaluation, communication, and competency development. This study used a descriptive quantitative design to analyze the performance of Indonesian language teachers. The population in this study were all Indonesian language subject teachers who taught at Madrasah Aliyah in Makassar City, totaling 46 people. The sample in this study were Indonesian language subject teachers who taught at 3 State Aliyah Madrasahs in Makassar City totaling 17 people. Data collection using a questionnaire given to Indonesian language subject teachers. The data collected were then analyzed by descriptive statistics. Before analyzing the data, researchers will process the data through editing, coding, and tabulating. The data will be presented in the form of frequency distribution tables and percentages. The results showed that the performance of Indonesian language teachers was still moderate. It needs improvement in planning, implementation, evaluation, communication, and competency development. Strategic steps are needed: improving students' initial analysis and technology in lesson plans, focusing on time management, interesting learning methods, evaluation with appropriate items, good communication, and competency development with class action research and scientific work. A comprehensive approach through professional development, innovative learning, continuous evaluation, open communication, and competency development is key in improving the performance of Indonesian language teachers.